A sensing device for gasoline engine speed of a miniature Portable Unmanned Helicopter. (16th November 2010) - Lin, Chang-Jun; Ozaki, Hiroaki; Qiu, Hua; Yue, Yong
This paper presents a sensing device for gasoline engine speed used in a miniature Portable Unmanned Helicopter (PUH). The sensing device has several favourable features appropriate for PUH control, i.e., small, light, accurate and easy to handle in the control operation, especially, easy and low-cost for manufacturing. Moreover, it is also applicable to general gasoline engines. Experimental results with a miniature PUH have demonstrated the effectiveness and practicability of the sensing device for the application in PUH control. The novel method has been submitted for Patent in Japan.